Save Everything: Supporting Human Memory with a Personal Digital Lifetime Store - Tan, Desney; Berry, Emma; Czerwinski, Mary; Bell, Gordon; Gemmell, Jim; Hodges, Steve; Kapur, Narinder; Meyers, Brian; Oliver, Nuria; Woodberry, Ken (Personal Information Management: Challenges and Opportunities (eds. William Jones and Jaime Teevan), 2007)
One of the things that distinguishes human beings from other species is the magnitude to which we manipulate our (largely synthetically created) environments and our technologies in order to augment ourselves physically and mentally. Supporting our individual as well as collective memory has been a particularly important endeavor as we have continued to build upon past experiences and improve our way of life. We are now at a time when each of us is generating and handling more information than ever before. Fortunately, we are now also equipped with technologies that can begin to record, store, summarize, and retrieve all this content. Various governments have recognized the potential of realizing these augmentations and created programs to fund work in the area, as for example in Memories for Life Grand Challenge in the UK, Fitzgibbon and Reiter (2003), and the LifeLog program in the United States (DARPA, n.d.), the work of which has now been distributed into multiple other programs